Major Changes in Plastid Protein Import and the Origin of the Chloroplastida - Michael Knopp; Sriram G. Garg; Maria Handrich; Sven B. Gould (iScience, 2020)
Summary: Core components of plastid protein import and the principle of using N-terminal targeting sequences are conserved across the Archaeplastida, but lineage-specific differences exist. Here we compare, in light of plastid protein import, the response to high-light stress from representatives of the three archaeplastidal groups. Similar to land plants, Chlamydomonas reinhardtii displays a broad response to high-light stress, not observed to the same degree in the glaucophyte Cyanophora paradoxa or the rhodophyte Porphyridium purpureum. We find that only the Chloroplastida encode both Toc75 and Oep80 in parallel and suggest that elaborate high-light stress response is supported by changes in plastid protein import. We propose the origin of a phenylalanine-independent import pathway via Toc75 allowed higher import rates to rapidly service high-light stress, but with the cost of reduced specificity. Changes in plastid protein import define the origin of the green lineage, whose greatest evolutionary success was arguably the colonization of land. : Biological Sciences; Plant Biology; Plant Evolution Subject Areas: Biological Sciences, Plant Biology, Plant Evolution